Objectivity as (self-)censorship - Pöttker, Horst (Javnost (Ljubljana), 2004)
The task of journalism in a democracy is to create publicness in the sense of unrestricted social communication. A broad and open interpretation of censorship means the creation of barriers to public communication not only by the state, but also by economic, social, and cultural conditions. This essay addresses professional principles of journalism - the separation of editorial and advertising sections, documentation and fiction, and facts and opinion - as means of self-censorship in a democracy. Where are the limits of these professional principles? What are the criteria that distinguish between their legitimate and illegitimate uses? This essay interprets the current tendency to dissolve the journalistic principle of separation.
Keywords: journalism; novinarstvo; informiranje; poklicna etika; novinarska etika; objektivnost